2004
DOI: 10.1262/jrd.50.533
|View full text |Cite
|
Sign up to set email alerts
|

Factors Required during Preculture of Rat Oocytes Soon after Sperm Penetration for Promoting Their Further Development in a Chemically Defined Medium

Abstract: Abstract. Blastocyst formation in a chemically defined medium (mR1ECM) of rat oocytes soon after sperm penetration is less frequent than in those undergoing male pronuclear formation. This inhibition is released by preculturing the oocytes for a few hours in modified Krebs-Ringer bicarbonate solution (mKRB). The present study examined the effects of phosphate (Pi), bovine serum albumin (BSA) and osmolarity during preculture of sperm penetrated rat oocytes on their development to blastocysts in mR1ECM in vitro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The Rat Resource and Research Center is now a robust national repository. Methods have been developed that allow the rat embryo to be cultured from one cell into a blastocyst (Iannaccone et al, 2001;Yang et al, 2004;Zhou et al, 2003). A high-quality draft sequence of the rat genome is available.…”
Section: Disease Models and Mechanisms Dmmmentioning
confidence: 99%
“…The Rat Resource and Research Center is now a robust national repository. Methods have been developed that allow the rat embryo to be cultured from one cell into a blastocyst (Iannaccone et al, 2001;Yang et al, 2004;Zhou et al, 2003). A high-quality draft sequence of the rat genome is available.…”
Section: Disease Models and Mechanisms Dmmmentioning
confidence: 99%
“…Hence, it could become beneficial to create culture conditions for oocytes and preimplantation embryos in vitro that more nearly reflect conditions in vivo. Such conditions likely differ among species, since one-cell rat embryos develop better in media of 304 than 246 mOsmol/kg (Yang et al, 2004), whereas the reverse is true for the fertilized mouse eggs discussed above. The osmolality of oviductal fluid in the cycling rat was reported to be 287 ± 1 mOsmol/kg (Waring, 1976), but this osmolality has not, to our knowledge, been measured during pregnancy.…”
Section: Clinical and Transgenerational Implicationsmentioning
confidence: 99%
“…Eggs were washed in M2 and placed in BMOC-3 (Invitrogen, Carlsbad, CA) under embryo tested mineral oil (Sigma) in a 37°C, 5% CO 2 , humidified incubator. For two-phase cell culture, eggs were transferred to mR1ECM prepared as described (Yang et al 2004) after overnight culture in BMOC-3.…”
Section: Superovulation and Egg Collectionmentioning
confidence: 99%
“…We tested four media used to culture rodent eggs (BMOC-3, M16, KSOM, and mR1ECM) and found that none of them supported development of fertilized rat eggs to the blastocyst stage (data not shown). Yang et al (2004) described a two-phase culture system that supports the development of 74% of fertilized Wistar rat eggs to blastocyst stage. We tested the development of SD and F344 eggs cultured in BMOC-3 overnight and then cultured in mR1ECM for 5 days and found that 85% of tested SD eggs and 52% of tested F344 eggs developed to blastocyst (Table 4).…”
Section: Pseudopregnancy Inductionmentioning
confidence: 99%